Protocol for fast antibiotic resistance-based gene editing of mammalian cells with CRISPR-Cas9 - Petia Adarska; Eleanor Fox; Joshua Heyza; Carlo Barnaba; Jens Schmidt; Francesca Bottanelli (STAR Protocols)
Summary: Protein tagging with CRISPR-Cas9 enables the investigation of protein function in its native environment but is limited by low homology-directed repair (HDR) efficiency. Here, we present a protocol for fast antibiotic resistance-based gene editing with CRISPR-Cas9 (FAB-CRISPR), which streamlines N/C-terminal tagging using an antibiotic resistance cassette for rapid selection and enrichment of gene-edited cells. We describe in detail guide RNA and HDR donor plasmid cloning, transfection of editing reagents into HeLa cells, and subsequent enrichment and verification of gene-edited cells.For complete details on the use and execution of this protocol, please refer to Wong-Dilworth et al.,1 Stockhammer et al.,2 Stockhammer et al.,3 Heyza et al.,4 and Broadbent et al.5 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.